“Acribeia” in the 2nd Marriage Practice according the St Euthymius of Tyrnovo’s Letter to the Metropolitan of Ungro-Valachia Anthimu - Николчев, Дилян (Forum Theologicum Sardicense, 2025)
“Acribeia” in the 2nd Marriage Practice according the St. Euthy-mius of Tyrnovo's Letter to the Metropolitan of Ungro-Valachia Anthimus. The following brief study focuses on a letter from St. Patriarch Euthymius of Tarnovo to Anthimus, Metropolitan of Ugro-Valachia Anthimus. In this letter, Eu-thymius, the last primate of the Patriarchate of Tarnovo before Bulgaria's subjugation by the Ottomans, addresses the canonical issue of Orthodox Christians entering a second marriage. This study aims to correct certain interpretations of the text, particularly regarding the validity of a second marriage.